2019
DOI: 10.1016/j.ijggc.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sedimentary heterogeneities in the sealing formation on predictive analysis of geological CO2 storage

Abstract: Numerical models of geologic carbon sequestration (GCS) in saline aquifers use multiphase fluid flow-characteristic curves (relative permeability and capillary pressure) to represent the interactions of the non-wetting CO2 and the wetting brine. Relative permeability data for many sedimentary formations is very scarce, resulting in the utilisation of mathematical correlations to generate the fluid flow characteristics in these formations. The flow models are essential for the prediction of CO2 storage capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…In the absence of site-specific data on capillary pressure, relative permeability and pore geometry distribution, the study proposes a parameterisation scheme for the pore geometry index that can serve as a tool for modelling hydraulic heterogeneities in clastic formations. For the sake of a comprehensive demonstration, this methodology has been applied to flow simulation through stratigraphic heterogeneities such as graded bedding in the reservoir (Onoja and Shariatipour, 2018) and transitional lithologies in the seal (Onoja et al, 2019). The authors observed that the exclusion of relative permeability and capillary heterogeneities in the dynamic modelling of CO2 sequestration can underestimate the storage performance of the reservoir and the seal.…”
Section: The Relative Impact Of N Swr and Snrmax On The Co2 Storage P...mentioning
confidence: 99%
“…In the absence of site-specific data on capillary pressure, relative permeability and pore geometry distribution, the study proposes a parameterisation scheme for the pore geometry index that can serve as a tool for modelling hydraulic heterogeneities in clastic formations. For the sake of a comprehensive demonstration, this methodology has been applied to flow simulation through stratigraphic heterogeneities such as graded bedding in the reservoir (Onoja and Shariatipour, 2018) and transitional lithologies in the seal (Onoja et al, 2019). The authors observed that the exclusion of relative permeability and capillary heterogeneities in the dynamic modelling of CO2 sequestration can underestimate the storage performance of the reservoir and the seal.…”
Section: The Relative Impact Of N Swr and Snrmax On The Co2 Storage P...mentioning
confidence: 99%
“…Other authors (Doughty & Pruess, 2004; Doughty et al., 2001; Gershenzon, Ritzi, et al., 2015) have only analyzed dissolution trapping in a few idealized depositional settings. In numerical modeling studies, the small‐scale variability of permeability is often not explicitly represented (Birkholzer et al., 2009; Hayek et al., 2009; Lee et al., 2010; Onoja et al., 2019; Pruess & Nordbotten, 2011; Rasmusson et al., 2015). Qualitative or quantitative analysis of the impact of discounting the small‐scale variability on modeling prediction of geological carbon sequestration has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Once the CO 2 is injected in underground formations, it begins moving laterally beneath the caprock generally towards less deeper locations [9][10][11][12][13]. Therefore the CO 2 plume would encounter other wells as it moves along its path.…”
Section: Introductionmentioning
confidence: 99%